Investigation of Industrial Residues and Waste Materials to Expand the Raw Material Base for the Production of Lightweight Aggregates - Jacob Fenner; Andrej Zeller; Steffen Liebezeit; Manuela Knorr; Alexander Schnell; Luka Mettke; Daniel Goldmann (Materials Proceedings, 2024)
More than 218 million tonnes of mineral construction waste are produced in Germany every year. In view of the shortage of domestic raw materials and an increasing demand for lightweight aggregates and gypsum, it is important to find alternative sources of raw materials for the production of light aggregates. The main focus of our investigations is on construction and demolition waste and industrial by-products, which have so far only been used at a low level. Chemical analyses can be used to classify potential substances in the ternary diagram according to RILEY and to examine their basic suitability. However, the results show that the suitability of a raw material for the production of lightweight aggregates cannot be determined solely on the basis of the classification in the ternary diagram. Experimental investigations are necessary in any case. From the range of residual and waste materials investigated, the rhyolite fractions showed the best bloating properties. Without the addition of bloating agents, bloating values of 1.4 can be achieved. The addition of iron slurry to a reduction in the bloating temperature by about 100 °C, however, is associated with a slight reduction in the bloating value. With our investigations, we were able to show that an expansion of the raw material base for the production of lightweight aggregates is also possible beyond the use of classic, heterogeneous building rubble containing bricks.